A Cross-Sectional Study of the Candidal Species Isolated in the Oral Cavities of Type II Diabetic Patients - Samnieng, Patcharaphol; Sonthayasathapon, Sita; Siriwat, Masjutha; Jeamanukulkit, Supanee (UI Scholars Hub, 2017)
Background: The objectives of this study were to determine the prevalence and colonisation of Candida species and to study the factors related to candidal colonisation in the oral cavity among type II diabetic patients. Methods: The data of 102 diabetic patients was collected from the Outpatient Diabetic Clinic at the Naresuan University Hospital. Data was collected via a questionnaire and oral examination. The subjects were measured for their fasting blood sugar levels and salivary pH. Candida colonisation was assessed using saliva sampling, and was cultured on CHROMagar Candida plates. Species and colony forming unit/mL were recorded. Results: The results showed that the prevalence of oral Candida species in diabetic patients was 73.5%. The most frequent candidal species in diabetics were Candida albicans (68.6%), followed by C. glabrata (28.4%), C. tropicalis (10.8%), and C. krusei (2.0%) respectively. There was no statistical significance between the fasting plasma glucose levels and oral Candida species colonisation. Logistic regression showed that a decrease of the salivary pH was related to the colonisation of candidal species. Results showed that the use of a dental prosthesis was a related factor to the colonisation of candidal species (p < 0.05). Conclusions: A high prevalence of candidal species were found in type II diabetic patients. Salivary pH and use of a dental prosthesis are factors that promote candidal infections in type II diabetic patients